KREDIT PEMILIKAN RUMAH (KPR) PERSPEKTIF SYARI’AH - Doddy Afandi Firdaus (J-EBI (Jurnal Ekonomi Bisnis Islam), 2021)
Home is one of the three primary human needs in life. There is no doubt that everyone wants to have their own home as a shelter and rest. These constraints cause mortgages (Home Ownership Credit) to be an option that can not be negotiable. Credit as one of the products offered by the bank to its customers turned out to have a role or benefit that is not small. This situation requires a clear legality according to Islam (Islamic law), because in practice often with the contract/credit transaction is sometimes even to burdensome even burdensome society in this case as a customer of a bank or consumer of goods that are traded on credit.